Gene expression analysis of effectors involved in early interaction of banana and Fusarium oxysporum f. sp. Cubense / Poon Nee Kiew - Poon , Nee Kiew (2020)
Banana is a popular but disease-laden fruit crop. It is very susceptible to various phytopathogens such as viruses, bacteria, fungi and nematodes. A particularly infectious and economically important fungal disease in banana is Fusarium wilt caused by Fusarium oxysporum f. sp. cubense (Foc). The disease has been plaguing the banana industry since late 19th century. Despite the early discovery of this phytopathogen of banana, little is known on its the mechanism of pathogenicity. In other plants, fungal effectors have been found to function in manipulating plant mechanisms during infection and many have been identified and characterized. In this study, the presence of a well-studied group of effectors known as Secreted-in-xylem (SIX) were verified in the Foc Tropical Race 4 (FocTR4) genome. Additionally, a computational pipeline was used to predict a pool of Foc effector candidates known as Small secreted cysteine-rich protein (SSCRP). The gene expression of selected effectors were characterized during the early interaction of the banana host and Foc. The in silico prediction pipeline successfully predicted 101 putative SSCRP and five of them were selected for gene expression analysis. The expression profiles of eight FocSIX genes identified in the genome were characterized with quantitative reverse transcriptase PCR (qRT-PCR). Four out of five SSCRP were found to be expressed in planta and all eight FocSIX genes were upregulated during early pathogenic interaction. Genomic features of the effector genes were also examined in this study. The results suggest FocSIX genes were actively involved in the early interaction of banana and FocTR4. Future work should focus on the functional characterization of the SSCRP and FocSIX encoding genes.